2022
DOI: 10.3390/su14031114
|View full text |Cite
|
Sign up to set email alerts
|

NEV’s Supply Chain Coordination with Financial Constraint and Demand Uncertainty

Abstract: Sustainable development coordination can facilitate the new energy vehicles (NEV) supply chain. By a coordinating supply contract, the operating costs can be reduced and supply chain competitiveness can be improved. We designed a revenue-sharing and buy-back (RSBB) contract to coordinate the supply chain with the cash-strapped retailer or manufacturer and analyzed the impact of the acceptable bankruptcy risk and own fund on the optimal order quantity, supply chain profits, and coordinating factors, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Yang et al (2021) examined the coordination effect of wholesale price contracts in the presence of members' risk and capital constraints. Li and Li (2022) developed a BBRS contract to eliminate double marginalization in a new energy vehicle supply chain with a cash-strapped retailer.…”
Section: Supply Chain Coordination Under Financial Considerationsmentioning
confidence: 99%
“…Yang et al (2021) examined the coordination effect of wholesale price contracts in the presence of members' risk and capital constraints. Li and Li (2022) developed a BBRS contract to eliminate double marginalization in a new energy vehicle supply chain with a cash-strapped retailer.…”
Section: Supply Chain Coordination Under Financial Considerationsmentioning
confidence: 99%
“…The prevailing volatility in the business environment is one of the major factors that impact the operations management of manufacturers [16]. Many researchers have discussed manufacturers' operational decision making in consideration of demand uncertainty [13][14][15][17][18][19][20][21][22][23][24]. Ramezani et al [17] developed a stochastic multi-objective optimization model to identify Pareto equilibrium under an uncertain environment in which prices, costs, market demands, and return rates are uncertain.…”
Section: Demand Uncertaintymentioning
confidence: 99%
“…They concluded that offering incentive mechanisms can effectively induce the retailer to participate in the green technology investment. Li and Li [23] considered the financial constraints and demand uncertainty of sustainable supply chain members and proposed a revenue-sharing (RS) and buy-back (RSBB) contract to coordinate the supply chain. Wu and Shang [24] modeled a green supply chain consisting of a supplier, a government, a leader retailer, and a follower retailer to investigate the greening operational decisions and information leakage decisions under demand uncertainty.…”
Section: Demand Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation